Translation Errors and Mistakes in Polish Language Versions of EU Legal Texts - Matulewska, Aleksandra; Nowak, Paulina (SORUS S.C. Wydawnictwo i Drukarnia Cyfrowa, 2006)
This paper deals with the analysis of mistakes and errors in the translation of the Council Regulation (EC) no 1346/2000 of 29 May 2000 on insolvency proceedings and the EU Strategy to combat illicit accumulation and trafficking of SALW and their ammunition 5319/06 of 13 January 2006 from English into Polish. This article presents a selection of examples from the English and French versions together with their incorrect translations into Polish with the authors’ suggestions of correct equivalents. The identified problems result from the translation method applied (or no translation method applied), syntactic and grammatical differences between Polish and English, as well as culturally-conditioned differences in Polish and English legal realities.

Praca dotyczy analizy błędów, które pojawiły się w tłumaczeniu na język polski dwóch dokumentów unijnych: Council Regulation (EC) no 1346/2000 of 29 May 2000 on insolvency proceedings oraz the EU Strategy to combat illicit accumulation and trafficking of SALW and their ammunition 5319/06 of 13 January 2006. W artykule przedstawiono wybrane fragmenty wersji francuskiej, angielskiej oraz błędnej polskiej wraz z sugerowanymi przez autorki ekwiwalentami. Problemy przedstawione w artykule wynikają z zastosowania niewłaściwej metody tłumaczeniowej (lub też braku jakiejkolwiek metody), różnic składniowych pomiędzy językami polskim i angielskim, jak również z uwarunkowanych kulturowo różnic w rzeczywistości prawnej języka polskiego i angielskiego.
Keywords: Translation errors; Polish language versions of EU legal texts; Translation of legal documents; English-Polish translation; Mistakes in translation